Characterization of host substrates of SARS-CoV-2 main protease - Melano, Ivonne; Lo, Yan-Chung; Su, Wen-Chi (Frontiers in Microbiology, 2023)
The main protease (M pro ) plays a crucial role in coronavirus, as it cleaves viral polyproteins and host cellular proteins to ensure successful replication. In this review, we discuss the preference in the recognition sequence of M pro based on sequence-based studies and structural information and highlight the recent advances in computational and experimental approaches that have aided in discovering novel M pro substrates. In addition, we provide an overview of the current understanding of M pro host substrates and their implications for viral replication and pathogenesis. As M pro has emerged as a promising target for the development of antiviral drugs, further insight into its substrate specificity may contribute to the design of specific inhibitors.